Work-based Learning (WBL) hospitality graduates attachment: industry perspectives / Jazira Anuar, Norzuwana Sumarjan and Mohd Onn Rashdi Abd Patah - Anuar, Jazira; Sumarjan, Norzuwana; Abd Patah, Mohd Onn Rashdi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The tourism and hospitality sector plays a crucial role in the services industry, functioning as one of the primary contributors to the Malaysian economy. The hospitality industry's performance is closely tied to its significant contribution to job creation, particularly through the employment of hotel staff. The students participating in work-based learning (WBL) industrial attachment or training were utilized as a valuable resource for the hotel's workforce in the form of workers. Given the ever-evolving nature of the education sector, it is crucial to actively participate in the development of curricula that are in accordance with the requirements of the industry. This study investigates instructional practices in the field of hospitality and the concomitant expectations that are linked to these practices. The purpose of this study is to present qualitative data on the perspectives of employers in the hotel industry regarding the industrial attachment experiences of Work-Based Learning (WBL) graduates. This study utilizes a research approach grounded in qualitative technique. The data employed in this study were acquired from a combination of primary and secondary sources. Specifically, primary data was collected through conducting in-depth interviews, while secondary data was gained through evaluating documentary evidence. A series of interviews were conducted with twelve (12) department heads representing a range of hotels in the Klang Valley region. The interviews were transcribed, coded and analyzed using content analytic approaches with the aid of the NVivo 10 software application. The study's findings revealed several interesting insights from industry players perspectives, which have been categorized according to the positive perceptions and conflicts that arose during graduates’ industrial attachment period. These findings are classified into WBL Graduates Commitment and Work-ethic, competencies, technology literacy and communication skills. The report concludes by providing recommendations for future research.